PENERAPAN PRINSIP- PRINSIP TRANSPARANSI, AKUNTABILITAS, PARTISIPASI, BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 DI DESA PERNEK, KECAMATAN MOYO HULU, KABUPATEN SUMBAWA BESAR - Astri Nurintan; Rispawati Rispawati; Bagdawansyah Alqadri (Indonesian Journal of Social Sciences and Humanities, 2020)
This study aims to ascertain the principles of transparency, accountability, participation and factors that take into account the principles of transparency, accountability, participation based on Law Number 6 of 2014 in Pernek Village, Moyo Hulu District, Sumbawa Besar Regency. The subjects of this study were the Village Head, Head of Finance, Village Secretary. The subjects of this study were selected based on the timing of the administration in Pernek Village, Moyo Hulu District, Sumbawa Besar Regency. The informants in the study were traditional leaders, religious leaders, community leaders. The data techniques used, observation, and documentation. The results show that 1) The application of the principles of transparency, accountability, participation is in accordance with Law Number 6 of 2014 in Pernek Village, Moyo Hulu District, Sumbawa Besar Regency, this can be seen in the activities of implementing village governance, which are carried out by village officials, 2) Factors that influence the application of the principles of transparency, participatory accountability, in the Pernek Village are internal factors and external factors. Internal factors include facilities, understanding, village government programs. Then external factors in the form of community cooperation, community ideas, leadership of the village head.